2021
DOI: 10.1093/gerona/glab338
|View full text |Cite
|
Sign up to set email alerts
|

Frailty and Depression in Late Life: A High-Risk Comorbidity With Distinctive Clinical Presentation and Poor Antidepressant Response

Abstract: Background Investigate the longitudinal relationship between physical frailty, the clinical representation of accelerated biological aging, and antidepressant medication response in older adults with depressive illness. Methods An 8-week randomized placebo-controlled trial (escitalopram or duloxetine) followed by 10-months of open antidepressant medication treatment (augmentation, switch strategies) was conducted in an outpat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…There are several well-validated frailty assessment tools used for screening and quantifying frailty status. Many studies across different diseases have revealed that frailty is associated with a variety of poor health outcomes, such as falls, dementia, mortality, hospitalization, and poor quality of life (39)(40)(41). As such, it is important to evaluate frailty status comprehensively to optimize outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…There are several well-validated frailty assessment tools used for screening and quantifying frailty status. Many studies across different diseases have revealed that frailty is associated with a variety of poor health outcomes, such as falls, dementia, mortality, hospitalization, and poor quality of life (39)(40)(41). As such, it is important to evaluate frailty status comprehensively to optimize outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis 3 identified higher baseline depression severity, comorbid anxiety, and executive dysfunction as the most important clinical variables associated with poor treatment response in LLD. Other studies 4 , 5 , 6 , 7 have also identified cardiovascular risk factors (eg, metabolic syndrome), cerebrovascular disease, brain structural changes, physical comorbidity, and frailty as variables associated with poor treatment response. Some of these variables are common in depression across the lifespan (eg, comorbid anxiety and depression severity), but others are geriatric specific (eg, cerebrovascular disease burden and executive dysfunction), suggesting that remission with treatment in LLD may have specific mechanisms that are associated with age-related brain and systemic aging processes.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, our study excluded patients with clinically diagnosed depressive or anxiety disorders who were taking antidepressants in order to avoid confounding the observed associations. Another study also found that frailty itself, in turn, worsened antidepressant treatment responses and outcomes [ 52 , 53 ]. Furthermore, chronic pain, as the origin of various health hazards, was closely associated with comorbidities such as depression and sleep disorders, and further contributed to frailty and increased adverse outcomes among older adults [ 54 ].…”
Section: Discussionmentioning
confidence: 99%